Ukuqonda kothisha mayelana nokufundiswa kwekhono lokufunda ngokuhlolisisa kanye nokuqondisisa imibhalo yesiZulu emabangeni aphezulu - Nsele, Sanele (Journal for Language Teaching, 2024)
ENGLISH TITLE: Teachers’ understanding of teaching critical reading and reading comprehension using isiZulu literary texts in FET phase This study explores teachers’ understanding of teaching critical reading and reading comprehension using isiZulu literary texts in FET phase. The study adopted interpritivist worldview and employed qualitative research methods to generate data. Semi-structured interviews, lesson observations and document anaysis were used to generate data from selected teachers. Purposive sampling was used to select teacher participants who are teachig isiZulu Home Language literary texts in the FET phase. This study used inductive approach to analyse data and it is supported by two theories; Piagets’ cognitive theory and Vygotskys’ social contsructivsm theory. Piaget (1983) emphasises cognitive developmental stages that learners undergo when reading lterary texts and learning language skills. On the other hand, Vygotsky (1978) puts emphasis on the role that social and cultural aspects play in understanding the world during learning. Vygotsky highlights the role of the knowledgable person (teacher, parents or peers) to facilitate learning experience during learning. Findings shows that teachers are using traditiona method of teaching literary texts. Traditional method focuses only on the structure and acquisition of textual information. Traditional method does not develop critical reading and comprehension because literary text is viewed as a complete and factual piece. Traditional method does not afford learners opportunities to create new meanings and interrogate authors perspectives. IQOQA Lolu cwaningo luphenya ngokuqonda kothisha mayelana nokufundiswa kwekhono lokufunda ngokuhlolisisa kanye nokuqondisisa imibhalo yesiZulu emabangeni asesigabeni sokuFunda okuQhubekayo nokuQeqesha. Ngokusebenzisa indlelakubuka yomhumusho kanye nezindlela zobunjalo botho, lolu cwaningo lukhiqize ulwazi ngezindlela zezinhlololwazi ezisakuhleleka, ukubukela othisha befundisa kanye nokuhlaziywa kwamadokhyumenti. Kulolu cwaningo kwalandelwa indlela yokuqoka ngenhloso othisha abafundisa imibhalo yesiZulu ulimi lwaseKhaya. Kwasetshenziswa isu lokuholela kokuthile; nohlaka lwemicabango kaPiaget (1983) kanye nekaVygotsky (1978) njengezinsizakuhlaziya okutholakele ocwaningweni. Injulalwazi kaPiaget (1983) ibalula ubumqoka bokuthuthukiswa kwengqondo yomfundi ukukwazi ukucabanga okufundwayo. Kanti-ke, injulalwazi kaVygotsky imayelana neqhaza lenhlalo kanye namasiko ekufundeni imibhalo. Indlela yokuhlaziya okutholakele ngezindikimba (thematic analysis) iye yaholela ekutheni kuhlaluke ukuthi othisha basasebenzisa indlela yendabuko yokufundisa ukuhluza isakhiwo kanye nohlaka kombhalo, nokwenza bangagxili ekuthuthukiseni amakhono elokuhlolisisa kanye nokuqondisisa imibhalo yesiZulu. Le ndlela yokuhluza imibhalo igxilisa ukuthola ulwazi lombhalo kanye nezimpawu ezisobala.